Pengaruh Penerimaan Pajak Bumi dan Bangunan Pedesaan dan Perkotaan Terhadap Pendapatan Asli Daerah Kabupaten Enrekang - Nur Askiah; Andi Indah Lestari (Program Studi Administrasi Fiskal, 2026)
This study aims to analyze the effect of land and building tax revenues in the rural and urban sectors on the original regional income of Enrekang Regency. The main problem raised is the level of compliance of land and building taxpayers which is still lacking, thus affecting the receipt of Land and Building Tax in Enrekang Regency. This study uses a quantitative approach with secondary data from the target and realization reports of PBB and PAD of Enrekang Regency in 2020-2021. The results of a simple linear regression analysis show that land and building tax revenues in the rural and urban sectors do not have a significant effect on PAD, with a significance value of 0.185> 0.05. With a t count of 1.713 <2.353. The regression equation obtained is Y = 19.934 + 0.237. Meanwhile, in terms of the contribution of Land and Building Tax to the Original Regional Income of Enrekang Regency from 2020-2024, it is still very low, namely an average of only 4% with very low criteria. In this case, it is important for BAPENDA as the PBB manager to conduct direct socialization/education to the community about the importance of paying PBB. Cooperation with village officials is also needed in the SPPT distribution process during the collection period. The media for disseminating information must also be adjusted to the conditions of the community. Routine annual evaluation of sub-districts/villages regarding the level of community compliance in paying PBB. Sub-districts/villages that have a high level of compliance can be given special awards or appreciation for being active in encouraging and educating the community regarding the importance of paying taxes on time. Sanctions or fines for late/non-compliance with PBB payments must also be emphasized consistently so that the community is more disciplined in fulfilling their tax obligations.